2019
DOI: 10.1016/j.ajoc.2019.100541
|View full text |Cite
|
Sign up to set email alerts
|

Glass intraocular foreign body removal with a nitinol stone basket

Abstract: Purpose Glass intraocular foreign bodies (IOFBs) complicate up to 14% of all IOFB cases and require specialized instruments for removal. We present a case of ocular trauma with two large glass IOFBs removed using a nitinol stone basket (NSB) designed for kidney stone extraction in the ureter and calyces. Observations An adult male suffered a restrained motor vehicle accident. Radiographic computed tomography identified a 9-mm polygonal IOFB within the posterior segment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Eckardt et al 6 described a commercially available nitinol memory snare to remove large IOFBs up to 12 mm but it needs to be purchased beforehand. Francis AW et al 7 reported the adoption of Bard SkyLiteTM Tipless Nitinol Stone Basket, a device designed for endoscopic retrieval of ureteric stones, to successfully remove two 6-mm glass foreign bodies from the posterior segment of the eye. Its tipless, retractable nature allows it to expand up to 12 mm in width and 18 mm in length and therefore it is capable of removing larger IOFB securely.…”
Section: Discussionmentioning
confidence: 99%
“…Eckardt et al 6 described a commercially available nitinol memory snare to remove large IOFBs up to 12 mm but it needs to be purchased beforehand. Francis AW et al 7 reported the adoption of Bard SkyLiteTM Tipless Nitinol Stone Basket, a device designed for endoscopic retrieval of ureteric stones, to successfully remove two 6-mm glass foreign bodies from the posterior segment of the eye. Its tipless, retractable nature allows it to expand up to 12 mm in width and 18 mm in length and therefore it is capable of removing larger IOFB securely.…”
Section: Discussionmentioning
confidence: 99%
“…Approaching the IOFB surgery in small-gauge vitrectomy gives the advantages of shorter operating times and faster visual recovery 9,12 ; however, the need to grasp and remove IOFBs of different location, size, and shape brings in technical hurdles and limitations. 10 The use of Eckardt forceps, designed for ILM peeling with end-gripping platform and thin tips, allows the surgeon to manipulate the retina and IOFB adherences with delicate approaches and improved visualization; however, specific tools are sometimes required to grasp and maneuver IOFBs inside the eye.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,8 Metallic IOFBs can be removed using magnets, 3 and the nonmetallic IOFBs require the use of forceps. 6 Intraocular foreign body removal through minimally invasive vitrectomy has already been described 9 ; however, the commonly used vitreoretinal forceps may be inadequate to ensure a secure grasp of the object. The wide variety of proposed IOFB forceps and tools are in 19/20 gauge and allow for the IOFB extraction by the extending of the scleral wound or through a sclerocorneal tunnel.…”
mentioning
confidence: 99%
“…24 Urologic nitinol stone baskets, which are used for renal calculi removal from the ureters and kidney, have been repurposed for the removal of IOFBs or lens material in multiple reports. [25][26][27] In these cases, commercially available urologic nitinol baskets, which are composed of tipless extendable loops of nitinol wire at the distal end of a sheath, are used to trap glass or plastic foreign bodies for removal (Fig. 9).…”
Section: Posterior Chamber Iofbsmentioning
confidence: 99%
“…The surgeon then pulls back the retracted basket-foreign body complex to the mid-vitreous, the sclerotomy site is enlarged, and the IOFB is removed under direct visualization. 27 While repurposing a urologic instrument for ophthalmic purposes has been effective, there have been multiple successful attempts at creating a dedicated ophthalmic nitinol device for IOFB removal. 23,28 The ACAR foreign body forceps is a 20-gauge instrument with 2 extendible perpendicular nitinol loops that are controlled by a sliding button at the center of the handle (Fig.…”
Section: Posterior Chamber Iofbsmentioning
confidence: 99%